Standardization parameters for cocoa pods (Theobroma cacao L.) - Nida Isti Azah; Resmi Muchtarichie; Yoppi Iskandar (Jurnal Ilmiah Farmasi, 2020)
Abstract  Background: Cocoa (Theobroma cacao L.) pods are a waste from chocolate production which has medicinal benefits. Cocoa pods have scientifically proved to have pharmacological activities.Objective: Standardization of plants to be used as medicine is required to control the quality and ensure the safety, efficacy, and quality.Methods: Data on the standardization parameters of cocoa pods were collected from journals published during the period 2010-2020 by searching in Google, Google Scholar, and Research Gate.Results: Standardization parameters of cocoa pods consisted of macroscopic and microscopic examinations, ash content, solute concentration in solvents, phytochemical screening, and thin layer chromatography.Conclusion: Macroscopic examination showed that the skin of cacao fruit has a brownish-yellow color and purplish red, a specific odor, and a bitter taste with four forms, namely amelonado, angoleta, cundeamor, and calabacil. Microscopic examination showed a collection of stone cells and hair covering. The moisture content of cocoa pods fulfills the requirement which is below 10%. The total ash content is 5.80 - 7.41, and the acid-insoluble ash content is 0.45 - 0.64. The concentration of solute in water is higher than in ethanol with 22.69 and 5.21, respectively. The phytochemical screening showed that cocoa pods have flavonoids, saponins, quinones, tannins, steroids, triterpenoids, monoterpenes, and sesquiterpenes. The thin-layer chromatography indicated the presence of phenolic compounds, catechol tannins, flavonoids, and terpenoids.Keywords: Cocoa pods, standardization, Theobroma cacao IntisariLatar belakang: Kulit buah kakao (Theobroma cacao L.) merupakan limbah dari produksi cokelat yang bermanfaat sebagai obat dan terbukti secara ilmiah memiliki berbagai aktivitas farmakologi.Tujuan: Standardisasi tanaman yang akan digunakan sebagai obat berguna untuk mengontrol kualitas serta memastikan keamanan, khasiat, dan mutunya.Metode: Data parameter standar kulit buah kakao dikumpulkan dari jurnal yang diterbitkan selama kurun waktu 2010-2020 dengan pencarian menggunakan situs pencarian seperti google, google scholar, dan researchgate.Hasil: Parameter standardisasi kulit buah kakao meliputi pemeriksaan makroskopik, mikroskopik, nilai kadar abu, kadar zat terlarut dalam pelarut, penapisan fitokimia, dan kromatografi lapis tipis.Kesimpulan: Pemeriksaan makroskopik, kulit buah kakao memilki warna kuning kecokelatan dan merah keunguan, bau khas, rasa pahit, dengan empat bentuk yaitu amelonado, angoleta, cundeamor, dan calabacil. Pemeriksaan mikroskopik menunjukkan adanya kumpulan sel batu dan rambut penutup. Kadar air kulit buah kakao sesuai dengan syarat yaitu berada dibawah 10%. Nilai kadar abu total 5,80 - 7,41 dan kadar abu tak larut asam 0,45 - 0,64. Kadar zat terlarut dalam air lebih tinggi dari etanol dengan nilai masing-masing 22,69 dan 5,21. Dari hasil penapisan fitokimia kulit buah kakao menunjukkan adanya senyawa flavonoid, saponin, kuinon, tannin, steroid, triterpenoid, monoterpen dan seskuiterpen. Pada kromatografi lapis tipis menunjukkan adanya senyawa fenolik, tannin katekol, flavonoid, dan terpenoid.Kata kunci : Kulit buah kakao, standardisasi, Theobroma cacao